EKSPLORASI DAN UJI PATOGENESITAS Beauveria bassiana TERHADAP ULAT GRAYAK (Spodoptera litura F.) - Retno Widya Ningrum; Noni Rahmadhini; Wiwin Windriyanti (BPFP Universitas Bengkulu, 2024)
[EXPLORATION AND PATHOGENICITY TEST OF Beauveria bassiana AGAINST ARMYWORMS (Spodoptera litura F.)]. Armyworm (Spodoptera litura) is a pest that can attack a variety of host plants. S. litura has a chewing bite mouth type and the phase that causes the most damage is instar 2, if no control is done then S. litura can cause damage up to 80% or cause crop failure. Control of S. litura still relies on chemical pesticides, this can have negative effects in the long term so alternative control is needed. Beauveria bassiana is an entomopathogenic fungus found in soil and has been studied to be able to control various types of insects at almost all stages of insects, including larvae and imago. The purpose of this study was to determine the effectiveness of B. bassiana fungus in controlling S. litura. The method used was the spore density level of 106, 107, 108 conidia/mL and the type of isolate B1 (isolate origin from Pacet) and B2 (isolate origin from Trawas), while the observation parameters were mortality rate and feeding rate. The results obtained were the treatment of isolate B1 at a spore density of 108 conidia/mL was able to cause the highest mortality of 80% while the rate of feeding power of isolate B1 treatment with a spore density of 108 conidia/mL was able to reduce the appetite of S. litura most effectively.